GUS DUR'S MULTICULTURAL TRACES: Welcoming Social Harmony Through the Rights of Religious Minorities - Khoirotun Ni'mah; Faisa Noor Ika Putranti; Muhammad Miftah; Naza Amalia Adilfi Rachmi (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2023)
This research examines Gus Dur's role as an agent of national unity and integrity in the multicultural context of Indonesia. The research method used is content analysis of Gus Dur's policies and handwriting. The results of the research show that Gus Dur played an important role in promoting social harmony through his deep understanding of minority rights and diversity. He encouraged the protection of minority rights, promotion of interfaith dialogue, and recognition of local cultures as an integral part of Indonesia. The conclusion of this research is that Gus Dur's contribution in  strengthening national unity through an inclusive approach to diversity is very important. Recommendations to relevant agencies are to increase understanding of minority rights, support inter-religious dialogue, and involve religious leaders in efforts to build social harmony. Implementing these recommendations will help strengthen national unity and integrity, as well as maintain Indonesia as a country based on diversity and tolerance.